Brain metabolic response to repetitive transcranial magnetic stimulation to lesion network in cervical dystonia - Kokkonen, Aleksi; Corp, Daniel T.; Aaltonen, Juho; Hirvonen, Jussi; Kirjavainen, Anna K.; Rajander, Johan; Joutsa, Juho (Elsevier, 2025)
Background: A previous study identified a brain network underlying cervical dystonia (CD) based on causal brain lesions. This network was shown to be abnormal in idiopathic CD and aligned with connections mediating treatment response to deep brain stimulation, suggesting generalizability across etiologies and relevance for treatment. The main nodes of this network were located in the deep cerebellar structures and somatosensory cortex (S1), of which the latter can be easily reached via non-invasive brain stimulation. To date, there are no studies testing brain stimulation targeted to networks identified using lesion network mapping.
Objectives: To assess target engagement by stimulating the S1 and testing the brain's acute metabolic response to repetitive transcranial magnetic stimulation in CD patients and healthy controls.
Methods: Thirteen CD patients and 14 controls received a single session of continuous theta burst (cTBS) and sham to the right S1. Changes in regional brain glucose metabolism were measured using [18F]FDG-PET.
Results: cTBS increased metabolism at the stimulation site in CD (P=0.03) but not in controls (P=0.15; group difference P=0.01). In subcortical regions, cTBS increased metabolism in the brainstem in CD only (PFDR=0.04). The remote activation was positively associated with dystonia severity and efficacy of sensory trick phenomenon in CD patients.
Conclusions: Our results provide further evidence of abnormal sensory system function in CD and show that a single session of S1 cTBS is sufficient to induce measurable changes in brain glucose metabolism. These findings support target engagement, motivating therapeutic trials of cTBS to the S1 in CD.